Language of instruction: A critical aspect of epistemological access to higher education in South Africa - Xulu-Gama, N.; Hadebe, S. (South African Journal of Higher Education, 2022)
The article discusses language as a critical aspect of epistemological access to higher education in South Africa through a critical analysis of students’ views on language preferences and attitudes at Durban University of Technology (DUT). Language of instruction at higher education institutions is one amongst a plethora of challenges faced in providing equity in higher education in a socially divided post-apartheid South Africa. This discussion of language and access takes place within broader epistemological access challenges faced in South African higher education. The data generated by 45 semi-structured interviews with undergraduate students from six faculties was collected as part of an institution-wide “Who are our students?” research project. The phenomenological thematic analysis arose from the three research questions asked: what is your home language and what language would you prefer to be taught in and why? Some students did not provide an explanation for their choice as they felt it was self-evident, while some provided interesting reasons for their choices. A critical analysis of the findings using Morrow’s epistemological access theory is conducted against the backdrop of the context of English dominance over indigenous languages; the history of South African higher education, current DUT and higher education policy as it pertains to language and the subsequent challenges around equitable access.